2013
DOI: 10.1155/2013/405794
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Seasonal Impact ofAcanthamoebaSpecies in a Subtropical Rivershed

Abstract: This study evaluated the presence of Acanthamoeba species in the Puzih River watershed, which features typical subtropical monsoon climate and is located just above the Tropic of Cancer in Taiwan. The relationship between the seasonal and geographical distributions of Acanthamoeba species in this rivershed was also investigated. Acanthamoeba species were detected in water samples using the amoebal enrichment culture method and confirmed by PCR. A total of 136 water samples were included in this study, 16 (11.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The lower detection rates of amoeboflagellates in comparison to Acanthamoeba spp. in the present study may be due to their domestic distribution instead of different habitat conditions (air, water, soil) for the latter [37,41] . Low detection rates were recorded in Nicaragua (9%, 4% and 5%), respectively [27] .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The lower detection rates of amoeboflagellates in comparison to Acanthamoeba spp. in the present study may be due to their domestic distribution instead of different habitat conditions (air, water, soil) for the latter [37,41] . Low detection rates were recorded in Nicaragua (9%, 4% and 5%), respectively [27] .…”
Section: Discussionmentioning
confidence: 75%
“…Our high detection rate was attributed to the time of study as the samples were collected from May to October, 2015, and most of Acanthamoeba spp. prevail during summer months [37] . Another explanation for the high detection rate of Acanthamoeba spp.…”
Section: Discussionmentioning
confidence: 98%
“…The latter study also found that the incidence of AK was much greater in areas supplied with hard water, which enhances limescale formation on pipes and so increases colonisation of Acanthamoeba [18]. Furthermore, distance from water purification plants, use of stagnant water (for example cisterns), and warmer air temperature were found can be associated with higher incidence of AK [14,[19][20][21][22][23][24][25][26]. In a more recent outbreak that started in the UK in 2010-2011 a three-fold increase in the incidence of AK was reported compared to the outbreak in 2004-2009 [27].…”
Section: Introductionmentioning
confidence: 73%
“…were isolated from 26.9% of tap water samples by Kilvington et al 34 The difference in detection rates of free-living amoebae in different countries and localities may be influenced by geographical conditions and raw water sources. [35][36][37] The results of the present study showed that the percentage of Acanthamoeba-positive samples in the inlet water of the DWTP were the same in all seasons of the year (33.3%). However, in the outlet drinking water, the percentage of positive samples reached 33.3% in spring and summer, while they were 0% in both winter and autumn.…”
Section: Discussionmentioning
confidence: 51%
“…Several workers in different countries reported seasonal variations in the distribution of Acanthamoeba in freshwater samples, with the highest percentage either in autumn [38][39][40] or in summer. 37,41,42 During the present study, a simple PCR technique was applied, using genus-specific primers, to confirm the results obtained by morphological identification of the isolated Acanthamoeba, but PCR confirmation at the species level is still needed. PCR has been found to be a more sensitive diagnostic test than culture.…”
Section: Discussionmentioning
confidence: 85%